Analisis Peran Personil Airport Rescue Fire Fighting Dalam Upaya Menjaga Keselamatan Penerbangan Di Bandar Udara Internasional Adi Soemarmo Boyolali - Aryo Rizal Fathoni; Septiyai Putri Astutik (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
The role of Airport Rescue Fire Fighting personnel at Adi Soemarmo Boyolali Airport is very important in maintaining flight safety, with the increase in facility equipment. This research aims 1). To analyze the role of Airport Rescue Fire Fighting Personnel in efforts to maintain flight safety at Adi Soemarmo Boyolali International Airport 2). To find out whether there are any obstacles and efforts made by officers to support the optimization of Airport Rescue Fire Fighting vehicles. This research was conducted at Adi Soemarmo Airport, Boyolali, this type of research uses qualitative methods, the data source in this research uses secondary data and primary data, data collection techniques are used (a combination of observation, interviews, documentation), data validity testing uses source triangulation, technique and time triangulation. The results of this research show that 1) Airport Rescue Fire Fighting personnel have a very important role in ensuring aviation safety and security, 2) obstacles to the ARFF unit facilities are obstacles related to the performance of the facilities, such as cars that are quite old so that the cars often don't work. can be started, so it takes more time to start the car. An effective way to overcome this is to push a car that won't start until it starts again.